Riesgos climáticos en la ciudad de Zaragoza - López Martín, Fernando (Geographicalia, 2017)
The risk of climatic origin happen in the city of Zaragoza causing lot of dammage with personal, material and economic repercussions.To implement the study, both the interventions of the Firemen Service and INM daily data have been taken into account. Out of them it has been intended to fixe the threshold of climatic origin risk (wind and precipitation) in Zaragoza.